Problematic Areas in Intercultural Management and International working mobility - Cmunt, Eduard (2015)
The goal of this thesis is to elaborate on the aspects of expatriate's successfulness in adaptation process. Firstly presenting theoretical background consisting of theories of international management and international mobility and after that introducing a research with six expatriates currently being on an assignment. It answers questions regarding successfulness of adaptation; mainly what personal and professional traits are valuable when being an expatriate. Based on the detailed study of their personal experiences, the key factors are discussed and suggested.